Implementation of Problem-Based Learning: What is the Influence on Students' Reasoning Ability in Elementary Schools? - Dela Tri Rahayu; Fitria Wulandari (research, training and philanthropy institution Natural Aceh, 2023)
This study aimed to determine the effect of applying the PBL learning model on the reasoning abilities of fourth-grade elementary school students Muhammadiyah 1 Krian. Types of experimental research and using one group pre-test-post-test design method. The population in this study were 23 fifth-grade students at SD Muhammadiyah 1 Krian. The researcher used a saturated sampling technique because population sizes were small. Reasoning ability data was obtained from essay tests before and after the application of PBL. Then the study results were analyzed using descriptive statistical techniques and the N-Gain test using the SPSS version 26 software. The results of this analysis indicate the reasoning ability of the pre-test post-test results showed a significant difference between the average value of the pre-test (63.26) and post-test (82.74), and. those using the N-Gain test obtained an average of 0.52 which indicates the moderate category, so using this PBL learning model can affect the reasoning abilities of elementary school students.